Diversity and the dynamics of capitalism. Issue 2 (September 2018) - Amable, Bruno
Abstract : The diversity of models of capitalism is evolving under the dynamics of capitalism itself, which imposes common trajectories to some institutional forms, such as the financial system or the employment relationship. This article argues that the analysis of the dynamic diversity and commonalities of capitalism can be made by focusing on four elements: the institutions defining the socio-economic model, the dominant social bloc that supports these institutional arrangements, the political actors and the strategy they have for uniting the dominant social bloc, and the public policies, in particular economic policies, implemented by the government.